Incidental findings during the diagnostic work-up in the head and neck cancer pathway: Effects on treatment delay and survival. (July 2021) - Schoonbeek, R.C.; Bult, F.F.S.; Plaat, B.E.C.; Witjes, M.J.H.; van der Hoorn, A.; van Dijk, B.A.C.; Halmos, G.B.
Highlights: Incidental findings (IFs) are present in 61.5% of head and neck cancer patients. Relevant IFs (21.6%) result in significant delay in treatment initiation. The majority of relevant incidental findings were found in the thorax (53.9%). The frequency of additional imaging and subsequent IFs increased over the years. Another independent factor associated with delay was initial (chemo)radiation. Abstract: Objectives: As a result of the increasing number of diagnostic scans, incidental findings (IFs) are more frequently encountered during oncological work-up in patients with head and neck squamous cell carcinomas (HNSCC). IFs are unintentional discoveries found on diagnostic imaging. Relevant IFs implicate clinical consequences, resulting in delay in oncologic treatment initiation, which is associated with unfavorable outcomes. This study is the first to investigate the incidence and nature of IFs over the years and establish the effect of relevant IFs on delay. Material and methods: This retrospective study compared two time periods (2010–2011 and 2016–2017), described associations between relevant IFs and delay in carepathway interval (days between first visit and treatment initiation) and assessed the effect of relevant IFs on overall two-year survival. Results: In total, 592 patients were included. At least one IF was found in 61.5% of the patients, most frequently on chest-CT. In 128 patients (21.6%) a relevant IF was identified, resulting for the majority in radiologist recommendations (e.g. additional scanning). Presence of a relevant IF was an independent significant factor associated with delay in treatment initiation. The risk of dying was higher for patients with a relevant IF, although not significant in the multivariable model (HR: 1.46, p = 0.079). Conclusion: In diagnostic work-up for HNSCC patients, relevant IFs are frequently encountered. As the frequency of additional imaging rises over the years, the number of IFs increased simultaneously. These relevant IFs yield clinical implications and this study described that relevant IFs result in significant delay in treatment initiation.